Modular Approach to Kekulé Diradicaloids Derived from Cyclic (Alkyl)(amino)carbenes - Hansmann, M. M.; Melaimi, M; Munz, Dominik; Bertrand, G. (Journal of the American Chemical Society, 2018)
A modular approach for the synthesis of Kekulé diradicaloids is reported. The key step is the insertion of a carbene, namely, a cyclic (alkyl)(amino)carbene (CAAC), into the C-H bonds of two terminal alkynes linked by a spacer. Subsequent hydride abstraction, followed by two-electron reduction of the corresponding bis(iminium) salts, affords the desired diradicaloids. This synthetic route readily allows for the installation of communicating spacers, featuring different degrees of aromaticity and lengths, and gives the possibility of generating unsymmetrical compounds with two different CAACs. Electron paramagnetic resonance (EPR), NMR, UV-vis, and X-ray studies in combination with quantum-chemical calculations give insight into the electronic nature of the deeply colored Kekulé diradicaloids. They feature a singlet ground state with varying degrees of diradical character in combination with small singlet/triplet gaps. Upon lengthening of the spacer, the properties of the compounds approach those of monoradicals in which steric protection of the propargyl radical moiety is necessary to inhibit decomposition pathways. Most of these diradicaloids are stable at room temperature, both in solution and in the solid state, but are highly oxygen-sensitive. They represent the first diradicaloids derived from iminium salt